Report on gun conditioning activities at PITZ in 2013 - Otevřel,M. (2015)
Copyright © 2014 CC-BY-3.0 and by the respective authors. Recently three RF guns were prepared at the Photo Injector Test Facility at DESY, location Zeuthen (PITZ) for their subsequent operation at FLASH and the European XFEL. The gun 3.1 is a previous cavity design and is currently installed and operated at FLASH, the other two guns 4.3 and 4.4 were of the current cavity design and are dedicated to serve for the start-up of the European XFEL photo-injector. All three cavities had been dry-ice-cleaned prior their conditioning and hence showed low dark current levels. The lowest dark current level - as low as 60μA at 65MV/m field amplitude - has been observed for the gun 3.1. This paper reports in details about the conditioning process of the most recent gun 4.4. It informs about experience gained at PITZ during establishing of the RF conditioning procedure and provides a comparison with the other gun cavities in terms of the dark currents. It also summarizes the major setup upgrades, which have affected the conditioning processes of the cavities.